Care of the soul a guide for cultivating depth and sacredness in everyday life - Moore, Thomas 1940-, Author (HarperPerennial, 1994)
A therapist draws on the world's religions, music, art, and his own experiences with patients to examine the connections between spirituality and the problems of individuals and society.